Web Montage: A Dynamic Personalized Start Page - Horvitz, Eric (Eleventh Inernational World Wide Web Conference, 2002)
Despite the connotation of the words "browsing" and "surfing," web usage often follows routine patterns of access. However, few mechanisms exist to assist users with these routine tasks; bookmarks or portal sites must be maintained manually and are insensitive to the user's browsing context. To fill this void, we designed and implemented the system. A web montage is an ensemble of links and content fused into a single view. Such a coalesced view can be presented to the user whenever he or she opens the browser or returns to the start page. We pose a number of hypotheses about how users would interact with such a system, and test these hypotheses with a fielded user study. Our findings support some design decisions, such as using browsing context to tailor the montage, raise questions about others, and point the way toward future work.